Microsoft Excel as a Digital Tool For MSMEs To Record Financial Reporting - Septiana MS; Kasmi (Journal of Society, Community and Business Development, 2025)
Under the direction of the Ministry of Manpower, the financial reporting training for MSMEs has proceeded smoothly and met its goals. The significance of maintaining systematic financial records and the many kinds of financial reports needed for business management were better understood by the participants as a result of this exercise. Additionally, the training improved the participants' technical proficiency in creating financial reports with Microsoft Excel. Participants were able to record transactions more accurately, elegantly, and readily for analysis by practicing with the supplied Excel templates. The abilities acquired from this course can support MSMEs' future competitiveness and business goals, improve their ability to get funding, and help them manage their finances more effectively It has been demonstrated that using Excel for digital record keeping improves the effectiveness, precision, and accountability of financial data. It is anticipated that this exercise would serve as the foundation for an MSME financial management system that is more sustainable and professional.